Composite membranes based on highly sulfonated PEEK and PBI: Morphology characteristics and performance - Zhang, Haiqiu; Li, Xianfeng; Zhao, Chengji; Fu, Tiezhu; Shi, Yuhua; Na, Hui (Journal of membrane science, 2008)
In the present work, the acid–base composite membranes were prepared using highly sulfonated poly(aryl ether ether ketone) (SPEEK) and polybenzimidazole (PBI). The morphology characteristics of composite membranes with different content of PBI were studied in detail by SEM, AFM, SAXS, FT-IR and UV. The results show that the structures of composite membrane become more compact than that of SPEEK, due to the acid–base interaction between the sulfonic acid groups and amine groups, which could lead to the increase of mechanical properties and the reduction of excess swelling. The performances of the composite membranes were characterized. The study showed that the proton conductivity of the composite membranes was dependent on the content of PBI. The thermal stabilities and mechanical properties of the SPEEK membranes were improved greatly. The composite membranes exhibited moderated swelling properties and ion exchange capacities. All the data proved that the composite membranes to be potential for usages in PEMFC.